AWARENESS OF WOMEN REGARDING ANALGESIA DURING LABOUR - Barakzai, Atiya; Haider, Gulfareen; Yousuf, Farhana; Haider, Ambreen; Muhammad, Nasiruddin (Journal of Ayub Medical College Abbottabad, 2010)
Background: Delivery pain is one of the most severe pains that women experience during their life so a change can affect all dimensions of pregnant women and her family life. Aim of this study was to assess the women’s knowledge of pain relief during labour, and their beliefs, fears, and misconceptions regarding epidural analgesia. Methods: It was descriptive study conducted in Obstetric and Gynaecology OPD of Liaquat University of Medical and Health Sciences, Hyderabad from September 2007 to January 2008. Women were selected randomly. All pregnant females who had delivered previously were interviewed. Primigravida were excluded from study. Information was collected on self-made questionnaire after an informed consent. Information was collected on computer software programme of SPSS 11.frequencies and percentages were calculated to express the results. Results: Total 131 women were included in this study. Out of these 65, (49.6%) had no education while 41 (31.2%) had primary education. Majority of women (82, 62.5%) had knowledge about injections while few (12, 9.1%) women had knowledge about epidural analgesia. Seventy-nine (60.3%) had chosen the injections as preferred method during next labour. Regarding attitude towards labour pains, 61 (46.5%) feels that labour pains as severe pain. Regarding epidural analgesia 4 (3%) women thought that epidural analgesia will lead to weakness of limbs and 3 (2.2%) women thought that it will cause permanent backache. Conclusion: There was poor general awareness of women about the role of epidural analgesia in labour leading to a low patient demand for such services. Most of the women had gained knowledge regarding pain relief from past experience or from friends and relatives. Keywords: Labour pains, epidural analgesia, awareness